Online Tools for Teaching and Learning - VASISHTA, P.A.; ROY, ANITHA; SIVASWAMY, VINAY (The journal of contemporary issues in business and government, 2021)
Learning online is education taking place over the Internet. Among other words it's sometimes referred to as "e-learning. "Online learning, however, is only one form of "distance learning"-the paragliding term for any learning that takes place over distance and not in a typical classroom. e-Learning is defined as a learning system focused on formalised instruction but using online tools. Online teaching usually refers to classes that are conducted exclusively online , meaning physical or on-campus class sessions are not available. A thorough literature search was performed using the database like Pubmed, google scholar, BioRxiv, MESH , Cochran database using the keywords ‘ online tools’ ,’ teaching’ and ‘Learning’ with no date and year restrictions. The language is restricted to English. 15 articles with similar data have been found which were analysed and have been included in this study. Mind maps were done using Xmind, Diagrams were drawn using brushes redux app and tabular columns were made using Google documents application. The recent articles discussed in this study help us in gaining further knowledge about assessment of the widely used online tool for learning and teaching. In conclusion, Edmodo, Google classroom are more widely used online tools for learning and teaching because it connects teachers and students and is assimilated into a social network.